2015
DOI: 10.1002/pc.23523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of injection molding conditions on the electrical properties of polycarbonate/carbon nanotube nanocomposites

Abstract: Polycarbonate/Carbon nanotube (PC/CNT) nanocomposites containing various CNT contents (0–5 wt%) were prepared by injection molding. The effects of CNT contents, injection speed (V) and injection temperature (T) on the electrical resistivity of the PC/CNT nanocomposites were investigated. It was found that the tensile strength of nanocomposites was enhanced slightly with increased CNT contents, and the tensile modulus was 29% greater after the 5 wt% CNT addition, but the brittle tendency became stronger. Aside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Polymer nanocomposites, as well as organic/inorganic hybrid nanocomposites materials gain considerable attention because of their practical interests in many applications. This is due to their unique electronic, mechanical, thermal, and optical properties . The importance of using nanoparticles as fillers is not only due to their ability to improve the final performance of the blend, but also due to their roles in enhancing the compatibility between the blend constituents .…”
Section: Introductionmentioning
confidence: 99%
“…Polymer nanocomposites, as well as organic/inorganic hybrid nanocomposites materials gain considerable attention because of their practical interests in many applications. This is due to their unique electronic, mechanical, thermal, and optical properties . The importance of using nanoparticles as fillers is not only due to their ability to improve the final performance of the blend, but also due to their roles in enhancing the compatibility between the blend constituents .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the shear stress induced on the molten material, by the flow during the mold-filling phase, which changes over the thickness and the surface of the mold cavity and the produced component [ 12 ]. In the case of polymers filled with conductive particles, this inhomogeneity in the morphology, results in an equivalent inhomogeneity in the electrical behavior [ 3 , 14 , 30 , 41 ]. As an example, Cesano et al [ 30 ] highlighted this effect in the thickness of PP-MWCNT nanocomposites, while Pötschke et al [ 44 ] studied this phenomenon on several positions over the surface of polycarbonate-MWCNT nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…This was also demonstrated for CNT-based nanocomposites [ 12 ]. Several studies have shown that the variation of the processing condition of injection-molded components, manufactured with CNT-based nanocomposites, can lead to drastic modification of the electrical conductivity, especially when the CNT content is in the range of the electrical percolation [ 13 , 14 , 15 , 16 , 17 , 18 ]. Villmow et al [ 16 ] studied injection-molded polycarbonate-based CNT nanocomposites, demonstrating that lowering the cooling rate and residence time seems to favor the attainment of higher electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the microhardness distribution from the surface to the interiorcould be divided into three regions—a rise, a decline, and a plateau. These phenomena might be explained as follows: when the MWCNT content was beyond 5 wt%, the MWCNTs in the core layer could more easily orient in a certain direction , and the thermal expansion coefficient of MWCNTs was lower than that of PC; thus a residual stress easily remained in the intermediate layer against with the pressure head of the meter, resulting in the enhancement of microhardness.…”
Section: Resultsmentioning
confidence: 99%